A Review on the Electrochemically Self-organized Titania Nanotube Arrays: Synthesis, Modifications, and Biomedical Applications - Fu, Yu; Mo, Anchun (Nanoscale research letters, 2018)
Titania nanotubes grown by anodic oxidation have intrigued the material science community by its many unique and potential properties, and the synthesis of technology is merging to its mature stage. The present review will focus on TiO 2 nanotubes grown by self-organized electrochemical anodization from Ti metal substrate, which critically highlights the synthesis of this type of self-organized titania nanotube layers and the means to influence the size, shape, the degree of order, and crystallized phases via adjusting the anodization parameters and the subsequent thermal annealing. The relationship between dimensions and properties of the anodic TiO 2 nanotube arrays will be presented. The latest progress and significance of the research on formation mechanism of anodic TiO 2 nanotubes are briefly discussed. Besides, we will show the most promising applications reported recently in biomedical directions and modifications carried out by doping, surface modification, and thermal annealing toward improving the properties of anodically formed TiO 2 nanotubes. At last, some unsolved issues and possible future directions of this field are indicated.